Программно-аппаратный комплекс для цифровой обработки сигналов - Торгаев С. Н. Станислав Николаевич; Евтушенко Г. С. Геннадий Сергеевич; Огородников Д. Н. Дмитрий Николаевич; Киселева В. А. Виктория Андреевна (2016, 2016)
Заглавие с экрана